RIGID PAVEMENT DESIGN WITH AASHTO 1993 IN SUBAIM – BULI ROAD - Kololikiye, Gilang Ramadan; Abdul Gaus; Muhammad Taufiq Yuda Saputra (Journal Innovation of Civil Engineering (JICE), 2024)
The condition of transportation in Indonesia concern due to the limited road and bridge infrastructure which can obstruct mobility. Regional Government must focus on improving the provision of regional transportation infrastructure. The construction of Subaim – Buli Road Section was carried out to enhance shore transportation infrastructure as a connection to Maba. The road section has a length of 10,700 m and a width of 3 x 2 m. CBR value of 6.23%, design life of 20 years and other design parameters required by AASHTO 1993. From the calculation results obtained plate thickness (D) = 7.335 cm < 15 cm. This indicates that with ESAL load = 129978 in 2037 there is still no need to use rigid pavement. Keywords: AASHTO 1993; Rigid Pavement; Subaim-Buli Road.